Renewing the old, creating the new: examining the strategies and results of urban conservation in Singapore and Shanghai - Zhao Yihua (Journal of City: Branding and Authenticity, 2023)
This paper explores the concept of authenticity in the conservation and renewal efforts in Singapore and Shanghai. Despite the past belief that demolishing or modifying historical buildings was acceptable for rapid urban development, the cities have recognized the value of preserving these buildings to maintain a sense of cultural heritage and authenticity. Through the analysis of typical conservation cases in both cities, the study examines the relevant strategies, methods, and results, and compares the changes and progress of conservation over time. The study finds that the conservation of historical buildings and districts can contribute to the authenticity and cultural identity of a city, fostering a sense of community and pride among residents. However, the concept of authenticity can be complex, and there may be debates over the appropriate level of restoration or modification required. Overall, the dissertation highlights the importance of balancing urban development and conservation and the evolving strategies towards people-based and coordinated development in both cities.